Tropical Rainfall and eDNA Washout Impact Estimations of Amazonian Biodiversity Patterns From Environmental Samples - Céline Condachou; Opale Coutant; Antoine Fouquet; Alice Valentini; Sébastien Brosse; Jérôme Murienne (Environmental DNA, 2025)
ABSTRACT Environmental DNA (eDNA) has been extensively used to facilitate the characterization of both terrestrial and aquatic communities. However, implementing temporal biodiversity monitoring remains a major challenge requiring a better understanding of how seasonal variations in biological and ecological factors influence eDNA detection. Focusing on a French Guiana river, our research investigates the impact of tropical rainfall on ecological patterns of aquatic and terrestrial communities using eDNA samples. We collected water eDNA samples during the dry and rainy seasons to detect fish, mammals, and amphibians. Between seasons, gamma diversity was stable for fish but increased in the rainy season for mammals and amphibians. This shift is explained by the transport of eDNA from terrestrial to aquatic systems through rainfall (eDNA washout) and by the increase of activity during the rainy season for amphibians. In terms of beta diversity, we found species homogenization between sites, affecting both terrestrial and aquatic taxa during the rainy season. This is driven by the increase in water discharge and decrease in water temperature, leading to eDNA drift over longer distances. We recommend sampling eDNA during the dry season for local community inventories and during the rainy season for regional species monitoring, particularly to maximize terrestrial species detection.